Comparison of subjective and functional results on the operative and non-operative application of clavicle fractures - Haris Dwi Khoirur Rofiq; Erwin Ramawan (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
Abstract  A clavicle fracture is one of the most common bone injuries occurring in 2-5% of all adult fractures. Clavicle fractures rarely require surgery. Most of the cases were treated by conservative methods. Conservative treatment yields satisfactory results. However, some latest studies showed an incidence of nonunion of up to 15% and patient dissatisfaction of 31%. This study analyzed the outcome and incidence of complications between operative therapy compared to conservative treatment. This research design was a retrospective descriptive observative. The study population was all patients diagnosed with clavicle fracture of the middle third in RSUD Dr. Soetomo Surabaya from 2015 to 2019. The total sample was 153 patients, with 95 patients who underwent conservative measures and 58 patients who underwent surgery. From the results, there were significant differences between the mean SF-36 score [90.81 and 98.21 (p = 0.000)], the mean DASH score [6.94 and 2.42 (p = 0.000)] in patients with fractures clavicle middle third treated with conservative and operative treatment. The union and functional rates were also better in the operative group. This study shows that the operative treatment on clavicle fractures is superior compared to conservative therapy. Keywords: Clavicle fracture, operative treatment, DASH score, SF-36 scoreCorrespondence: dr.harisdwi@gmail.com